Peculiarities of muscle-tendon mechanics and energetics in elite athletes in various sports - Shestakov, M.; Zubkova, A. (IntechOpen, 2021)
The article presents results of the research on jumping strategies applied by elite athletes in various sport disciplines. Research hypothesis: to perform the same motor task athletes employ different ways of organizing the movement and different features of MTU functioning. The choice of a mechanism to enhance muscle contraction depends on sport discipline, in particular specific features of the sport movement. The study involved members of the Russian national teams in alpine skiing, bobsleighing, mogul skiing and ski jumping. The athletes performed drop jumps from the heights of 0.1, 0.3, and 0.5 m with no arm swing. Experimental data were obtained online from 24 cameras using the Qualisys motion capture system (400 frames per second) and the two force plates AMTI 6000. Data was processed using the OpenSim package. The authors calculated the amount of accumulation and utilization of elastic strain energy and assessed metabolic energy expenditures in MTU. The authors concluded that employment of different strategies of movement organization in drop jumps could be explained by the transfer of motor skills specific to the athlete`s sport discipline. The results of the study may help coaches develop individual training plans for athletes, in particular strength training exercises targeting specific muscle groups.